Law and Accountability in Hajj Fund Reporting: Addressing Regulatory Disharmony in Indonesia - Meta Syarah (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2025)
This study analyzes the inefficiencies and ineffectiveness of Hajj fund reporting in Indonesia arising from regulatory disharmony between Law Number 34 of 2014 on Hajj Financial Management and Law Number 8 of 2019 on the Organization of Hajj and Umrah. Such inconsistency has created unclear reporting authority between the Hajj Financial Management Agency (BPKH) and the Ministry of Religious Affairs (Kemenag), resulting in weak oversight, transparency, and accountability in Hajj fund management. A normative legal approach based on statutory and literature analysis is employed. Through this method, the study finds that Kemenag is not legally required to report its fund utilization to BPKH, despite BPKH’s accountability. This asymmetry undermines transparency and oversight, while BPKH’s limited access to Kemenag’s reports and differing interpretations by Audit Board of Indonesia (BPK) and Finance and Development Supervisory Agency (BPKP) impair supervisory effectiveness. The study suggests regulatory harmonization institutional realignment and integrated reporting as necessary reforms. The Indonesian experience shows that institutional reform without regulatory coherence risks creating fragmented authority and accountability gaps. Countries with similar governance structures may draw important lessons learned from Indonesia’s case, the urgency of legal clarity, inter agency coordination, and integrated reporting as prerequisites for accountable and transparent Hajj fund governance.